2015
DOI: 10.1016/j.tox.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of inorganic mercury in pregnant rats and their offspring

Abstract: Environmental toxicants such as methylmercury have been shown to negatively impact fetal health. Despite the prevalence of inorganic mercury (Hg2+) in the environment and the ability of methylmercury to biotransform into Hg2+, little is known about the ability of Hg2+ to cross the placenta into fetal tissues. Therefore, it is important to understand the handing and disposition of Hg2+ in the reproductive system. The purpose of the current study was to assess the disposition and transport of Hg2+ in placental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Despite previous claims that Hg 2+ does not cross the blood–placental barrier, several in vivo and in vitro studies have provided evidence for the transport and accumulation of Hg 2+ in placentas and fetuses (Ask et al 2002; Inouye and Kajiwara 1990; Oliveira et al 2015). A recent study in pregnant Wistar rats exposed intravenously to two different doses of HgCl 2 showed that the accumulation of mercuric ions in the placental and fetal organs was dependent on the time of exposure and the dose to which pregnant rats were exposed (Oliveira et al 2015).…”
Section: Transport Of Inorganic Mercurymentioning
confidence: 93%
See 2 more Smart Citations
“…Despite previous claims that Hg 2+ does not cross the blood–placental barrier, several in vivo and in vitro studies have provided evidence for the transport and accumulation of Hg 2+ in placentas and fetuses (Ask et al 2002; Inouye and Kajiwara 1990; Oliveira et al 2015). A recent study in pregnant Wistar rats exposed intravenously to two different doses of HgCl 2 showed that the accumulation of mercuric ions in the placental and fetal organs was dependent on the time of exposure and the dose to which pregnant rats were exposed (Oliveira et al 2015).…”
Section: Transport Of Inorganic Mercurymentioning
confidence: 93%
“…Numerous in vivo studies in rats have shown that mercuric ions accumulate in hepatocytes following exposure to HgCl 2 (Bridges et al 2008a, b, 2011, 2014, 2015; Oliveira et al 2016, 2015; Zalups 1993a, b). When mercuric ions are presented to the sinusoidal membrane of hepatocytes, they are most likely bound to non-protein thiols and plasma proteins, such as albumin, ferritin, and γ-globulins.…”
Section: Transport Of Inorganic Mercurymentioning
confidence: 99%
See 1 more Smart Citation
“…The prenatal exposure of methyl mercury, placenta being a very ineffective barrier, can result in negative fetal impact to central nervous system maturation. [10][11] Pregnant wistar rats showed that mercury is capable of crossing the placenta, accumulating in fetal organs notably highest concentration in kidney, succeeded liver and brain [12]. Similar to mercury, lead exposures in rats have a profound effect in their memory and overall cognition.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to evaluate in virgin, pregnant, and lactating rats the effects of HgCl 2 exposure and the different responses against inorganic Hg. Since it is known that the kidney is the primary site of accumulation of inorganic Hg in dams (Bridges and Zalups, ; Favero et al, ; Oliveira et al, ; Zalups, ), we investigated kidney morphology, ultrastructural characterization and expression of markers related to oxidative stress and cellular organelle alterations. Furthermore, due to the rapid uptake and accumulation of Hg by liver, besides kidneys, in the present study were evaluated also Hg hepatic alterations and oxidative stress induction.…”
Section: Introductionmentioning
confidence: 99%